Probing the nature of deficits in the 'Approximate Number System' in children with persistent Developmental Dyscalculia. Issue 5 (30th July 2015) - Bugden, Stephanie; Ansari, Daniel
Abstract: In the present study we examined whether children with Developmental Dyscalculia (DD) exhibit a deficit in the so‐called 'Approximate Number System' (ANS). To do so, we examined a group of elementary school children who demonstrated persistent low math achievement over 4 years and compared them to typically developing (TD), aged‐matched controls. The integrity of the ANS was measured using the Panamath (www.panamath.org ) non‐symbolic numerical discrimination test. Children with DD demonstrated imprecise ANS acuity indexed by larger Weber fraction (w) compared to TD controls. Given recent findings showing that non‐symbolic numerical discrimination is affected by visual parameters, we went further and investigated whether children performed differently on trials on which number of dots and their overall area were either congruent or incongruent with each other. This analysis revealed that differences in w were only found between DD and TD children on the incongruent trials. In addition, visuo‐spatial working memory strongly predicts individual differences in ANS acuity (w) during the incongruent trials. Thus the purported ANS deficit in DD can be explained by a difficulty in extracting number from an array of dots when area is anti‐correlated with number. These data highlight the role of visuo‐spatial working memory during the extraction process, and demonstrate that close attention needs to be paid to perceptual processes invoked by tasks thought to represent measures of the ANS. Abstract : In this study, children with persistent dyscalculia (DD) exhibited (a) larger Weber fraction and (b) greater error rates when the size of the individual dot stimuli were incongruent with the more numerous dot array during a non‐symbolic numerical discrimination task compared to typically developing children. These findings reveal that indices commonly used to assess internal numerical representations are affected by visual perceptual variables and affects children with DD to a greater extent than their typically developing peers. Multiple explanations for the present set of findings are discussed herein.